Temperature and photoperiod interactions with silicon-limited growth and competition of two diatoms - Shatwell, Tom; Köhler, Jan; Nicklisch, Andreas (Journal of Plankton Research)
Diatoms often dominate temperate lakes and rivers in spring, when increasing temperature and daylength coincide with decreasing silicate concentrations. Since interactions between these factors may be important, we cultivated Stephanodiscus minutulus and Nitzschia acicularis (freshwater diatoms) under silicon limitation at different temperatures and photoperiods in continuous and batch culture. The Monod parameters of Si-limited growth indicated that S. minutulus should be superior under Si limitation. The type of interaction between silicate, temperature and photoperiod differed between species and indicated that the advantage of S. minutulus increases under low temperatures and photoperiods. Competition experiments in semicontinuous culture confirmed these predictions and were described accurately with a model of factor interactions. Multiple regression analysis of field data from a shallow eutrophic lake showed that dissolved silicate (DSi), temperature, photoperiod and total phosphorus (TP) were the most important predictors of spring centric diatom biovolume, where lower temperatures and photoperiods favour this group and higher biovolumes coincide with DSi depletion and higher TP. Pennate diatoms depended more on light, winter population size and grazer abundance. Conditions in situ suggested that factor interactions play a role during spring under strong Si limitation. We propose that the type of interaction reflects specific niche adaptation. Understanding interactions between physical factors and nutrients will increase our understanding of phytoplankton diversity and predictive accuracy of phytoplankton dynamics including combined effects of climate and trophic change.